Once a Church, Always a Church?: Sacred Spaces and Their Implications for Peacebuilding in Cyprus - Mäkipää, Arttu (A journal of church and state, 2024)
Since 1974, the island of Cyprus has been de facto divided into the internationally recognized Republic of Cyprus, which is in practice Greek Cypriot (GC)-